The Actuality of some Principles and Ideas of Law Philosophy Issued by Mircea Djuvara (Journal of Legal Studies, 2018)
The author analyzes in this paper principles and ides of philosophy of law issued by Mircea Djuvara, which preserve their contemporaneity, being useful for the perfecting of the state institutions and of the democracy not only at national level, but also at European Union one. His ideas and logical demonstration on the rational fundamentals of law, the autonomy of the moral and legal conscience, the specificity of truth and of juridical knowledge, the philosophical substantiation of power and Constitution, the principles of the democracy and the connections between the political power and the law are just few of the original elements due to which Djuvara became an acknowledged and respected personality not only in Romania, but also in the experts clubs of the Europe between the two World Wars.